A diversity-oriented approach to indolocarbazoles via Fischer indolization and olefin metathesis: total synthesis of tjipanazole D and I. Issue 41 (28th September 2016) - Kotha, Sambasivarao; Saifuddin, Mohammad; Aswar, Vikas R.
Abstract : New synthetic strategies to indolocarbazoles have been reported via two-fold Fischer indolization under green conditions usingl -(+)-tartaric acid and N, N -dimethyl urea. Abstract : New synthetic strategies to indolocarbazoles have been reported via two-fold Fischer indolization under green conditions usingl -(+)-tartaric acid and N, N -dimethyl urea. Starting with cyclohexanone, a bench-top starting material, this methodology has been extended to the total synthesis of natural products such as tjipanazolesD andI as well as the core structure of asteropusazole and racemosinB . Here, atom economical reactions like ring-closing metathesis, enyne-metathesis, and the Diels–Alder reaction have been used as key steps. Diverse strategies demonstrated here are useful in medicinal chemistry and materials science to design a library of decorated indoles.